2021
DOI: 10.1038/s43018-021-00227-3
|View full text |Cite
|
Sign up to set email alerts
|

Castration-mediated IL-8 promotes myeloid infiltration and prostate cancer progression

Abstract: Immunotherapy is a treatment for many types of cancer, primarily due to deep and durable clinical responses mediated by immune checkpoint blockade (ICB) 1,2 . Prostate cancer is a notable exception in that it is generally unresponsive to ICB. The standard treatment for advanced prostate cancer is androgen-deprivation therapy (ADT), a form of castration (CTX). ADT is initially effective, but over time patients eventually develop castrationresistant prostate cancer (CRPC). Here, we focused on defining tumor-cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 50 publications
(11 reference statements)
1
52
0
1
Order By: Relevance
“…This chemotactic pathway can be counterbalanced through direct inhibition of the STAT3 transcription factor ( 83 ). Chemokines responsible for MDSC recruitment include CXCL5 ( 78 ), and interleukin 8 (IL8), which also induces castration-resistance and tumorigenesis ( 84 ). Inhibition of IL8 in addition to ICI delayed castration resistance and increased CD8 + T cell infiltration in PCa murine models ( 84 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This chemotactic pathway can be counterbalanced through direct inhibition of the STAT3 transcription factor ( 83 ). Chemokines responsible for MDSC recruitment include CXCL5 ( 78 ), and interleukin 8 (IL8), which also induces castration-resistance and tumorigenesis ( 84 ). Inhibition of IL8 in addition to ICI delayed castration resistance and increased CD8 + T cell infiltration in PCa murine models ( 84 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines responsible for MDSC recruitment include CXCL5 ( 78 ), and interleukin 8 (IL8), which also induces castration-resistance and tumorigenesis ( 84 ). Inhibition of IL8 in addition to ICI delayed castration resistance and increased CD8 + T cell infiltration in PCa murine models ( 84 ). Furthermore direct inhibition of MDSC via the multikinase inhibitor, cabozantinib, has demonstrated anti-tumor efficacy in mCRPC mouse models, when combined with anti-CTLA4 and anti-PD1 monoclonal antibodies ( 85 ) ( Figure 1D ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemokine receptor, CXCR2, the receptor for interleukin-8, is critical to promoting myeloid-derived suppressor cell function and resistance to immune checkpoint blockade in prostate cancer preclinical models [ 25 27 ]. Targeting CXCR2 is presently being tested in clinical trials of men with mCRPC and other solid tumors in combination with checkpoint blockade (NCT03473925).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of IL‐8 signaling in combination with ICI has been found to augment the intra‐tumoral density of CD8 + T cells and delayed the occurrence of castration resistance. 60 Results of a recent systematic review also identified IL‐8 as a poor prognostic biomarker of gastric cancer. 61 Mesenchymal stem cells (MSCs) are one of the sources of IL‐8 in tumors like gastric cancer.…”
Section: Combination Of Icis With Il ...mentioning
confidence: 99%